2015
DOI: 10.1071/an13312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentrations of ground oak acorn on growth performance, blood parameters and carcass characteristics of goat kids

Abstract: The objective of the present study was to evaluate the effect of different levels of ground oak acorn on growth performance, blood parameters and carcass characteristics. Twenty-four goat kids averaging 16.93 ± 1.25 kg initial bodyweight were randomly assigned to four experimental diets in a completely randomised design for 90 days. The experimental diets consisted of (1) 0% oak acorn (control), (2) 8% oak acorn, (3) 17% oak acorn and (4) 25% oak acorn on a DM basis. The goats were slaughtered after 105 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…There is no report on feeding OA in pregnant goats in the literatures. However, DMI reduction in goats fed OA-contained diets in the present study is inconsistent with other studies who reported that increasing OA level in the diet of growing kids (Froutan et al, 2015) or oak leaves in growing calves' diet (Sharma, Singh, & Sahoo, 2008) increased DMI, but feeding chestnut extract (a source of HT) had no effect on DMI in finishing steers (Krueger et al, 2010). In the present study, reduction of DMI in goats fed OA can be attributed to the decreasing palatability due to bitter or astringent taste (Becker & Makkar, 1999) and decreasing NDF digestibility (Table 3; Allen, 2000).…”
Section: Dry Matter Intake Apparent Nutrient Digestibility and Repcontrasting
confidence: 99%
See 2 more Smart Citations
“…There is no report on feeding OA in pregnant goats in the literatures. However, DMI reduction in goats fed OA-contained diets in the present study is inconsistent with other studies who reported that increasing OA level in the diet of growing kids (Froutan et al, 2015) or oak leaves in growing calves' diet (Sharma, Singh, & Sahoo, 2008) increased DMI, but feeding chestnut extract (a source of HT) had no effect on DMI in finishing steers (Krueger et al, 2010). In the present study, reduction of DMI in goats fed OA can be attributed to the decreasing palatability due to bitter or astringent taste (Becker & Makkar, 1999) and decreasing NDF digestibility (Table 3; Allen, 2000).…”
Section: Dry Matter Intake Apparent Nutrient Digestibility and Repcontrasting
confidence: 99%
“…Oak forests in the west of Iran comprised an area of approximately 3 million ha that mainly dominated by Quercus persica, Quercus infectoria and Quercus libani (Ghorbani, Fatahi, Tahmasebi, & Hoseinzadeh, ). The acorn production by oak forests in Iran is estimated to be 800,000 tons annually (Froutan, Azizi, Sadeghi, Fatehi, & Lashkari, ). Animal production in this area is almost exclusively based on natural vegetation and forests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no effects of experimental diets on the concentrations of serum triglycerides and cholesterol in rams and bucks. There are many biologically active phenolic compounds in oak acorns such as tannins, ellagic and gallic acids, and galloyl and hexahydroxydiphenoil derivatives (Rakic et al, 2006) that play a role in the regulation of blood lipid profile (Froutan et al, 2015).…”
Section: Ammonia-nitrogen (Nh3-n)mentioning
confidence: 99%
“…The degree of the interaction depends highly on the structures of both of polyphenols and feed proteins (Mueller-Harvey, 2006). Oak products contain considerable levels of secondary metabolites (Froutan et al, 2015;Elahi and Rouzbehan, 2008). concluded that increasing concentration of condensed tannins in sheep diets added advantageous impact on nutritive value by increasing flow of nonammonia nitrogen and retained nitrogen to duodenum, but this accompanied by detrimental influence in reducing apparent digestibility of organic matter, lignin and energy.…”
Section: Introductionmentioning
confidence: 99%